Health needs and public health functions addressed in scientific publications in Francophone sub-Saharan Africa - (:unkn) unknown (My University, 2013)
OBJECTIVE:To describe the reporting of public health research in Francophone sub-Saharan Africa (FSA).STUDY DESIGN:A bibliometric research study of scientific public health publications in FSA, which includes 24 countries and approximately 260 million people.METHODS:Two researchers analysed original articles published in 2007 in the medical or social sciences fields and indexed in Scopus. At least one co-author of articles had to be based in FSA. The analysis focused on research field, public health function (WHO classification), FSA country author's affiliation, language, journal type and global burden of disease (WHO classification).RESULTS:Of 1047 articles retrieved by the search, 212 were from the public health field. The number of articles per country varied from 0 to 36. Public health functions examined were health service research (24.5%), health monitoring (27.4%), prevention (15%) and legislation (0.5%). The distribution of health needs described in the articles was close to that of the WHO data for Africa for 2004: infectious and parasitic diseases (70% vs 54%), maternal and perinatal conditions (15% vs 17%), non-communicable diseases (15.6% vs 21%), and injuries (0.5% vs 8%).CONCLUSION:The areas reported in published articles from sub-Saharan Africa reflect the health needs distribution in Africa; however, the number of publications is low, particularly for prevention. In light of the current focus on evidence-based public health, this study questions whether the international scientific community adequately considers the expertise and perspectives of African researchers and professionals.
Keywords: African Research